Analisis Masalah dan Solusi Pengelolaan Keuangan, Marketing dan Operasional pada UMKM Aneka Keripik Pak Suhendar Di Purwakarta : Pengabdian - Aziz Kholid Akbar Rangkuti; Nakara Inggita Syafarani; Nadia Nurfadila; Yana Ernawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The implementation of KPB/Internship aims to help students apply academic theory to real field practice and provide solutions for MSMEs, especially in management, marketing, and accounting. This program was carried out at UMKM Aneka Keripik Pak Suhendar in Ciseureuh, Purwakarta. Through observation, interviews, and simple data analysis, issues were identified such as unorganized financial records and marketing limited to offline sales. The students recommended digital marketing strategies and a simple financial recording format. These efforts are expected to help the MSME grow more systematically and expand its market reach.